Micro Structure in Shinzo Abe's Policy Speech at the 195th Assembly Meeting (Critical Discourse of Teun A. van Dijk) - Lina Rosliana; Fajar Mahardika (Universitas Diponegoro, 2020)
Speech is a way of expressing ideas in the form of words or discourse that is prepared to be spoken in front of the audience. Speech contains a message that is tailored to the situation when the orator delivers the speech. In addition to the message to be conveyed, the ideology and thoughts of an orator are also reflected in his speech. Therefore, an orator must have expertise in delivering his speech.This research is aims to determine the purpose and background of the Shinzo Abe Policy Speech at the 195th Session of Diet. The speech was delivered by Abe after he was re-elected as Prime Minister of Japan after the general election on October 22, 2017.Researcher used the critical discourse analysis of Teun A. van Dijk's model to dissect the ideology contained in the speech to focus on text analysis. Based on the results of this research, it can be interpreted implicit meanings in the text through linguistic elements, such as tematic, skematic, semantic, sintaxs, stilistic, and retoric.